Teaching critical reading to third year English students - Dewi Putriana (English Education Journal, 2016)
This study concerns the teaching of Critical Reading in an Academic Reading class for third year students in the Department of English Education at UIN Ar-Raniry Banda Aceh. A purposive sampling technique was used to choose the sample. The subjects of this study were the lecturer and 25 students who were in the Academic Reading class. The instruments used to collect the data were observation sheets, an interview guide, and field notes. The collected data were analyzed and interpreted through qualitative procedures, by using data reduction, data presentation, verification and drawing of conclusions. The first finding of this research was that the lecturer implemented the teaching of Critical Reading by implementing four activities during the teaching-learning process. The lecturer further assessed the process of students’ Critical Reading learning achievement by asking them each to answer Open-Response Questions during the learning process in the classroom and also he assessed the results of the students’ Critical Reading learning by asking them each to write a reflective essay as a response towards the text after the class session finished. Each student’s writings were collected together as their own portfolio. Therefore, it is recommended that teaching Critical Reading as observed in this study can be done at other higher education institutes. Critical thinking can be taught separately or infused with the teaching of reading even in the teaching of writing and speaking.